The Extent of Adherence to the Scientific Approach in the Appeals of Contemporaries in the Ḥadīth of Al-Ṣaḥīḥayn - al-Ṣaḥib, Muhammad-Eid; Hamasha, Oumama Emad (Dirasat: Shari'a and Law Sciences, 2021)
This research deals with the accusations of the contemporary writers against the ḥadīth of al-Ṣaḥīḥayn in order to reveal to what extent they adhere to the scientific approach in studying ḥadīth narratives, and to evaluate their works in the light of the principles of ḥadīth science. However, it has been concluded that the accusers did not adhere to the scientific approach in criticizing the ḥadīth in terms of several aspects. Among the most prominent forms of deviation from the scientific method, in which the accusers indulge, are: violating the rules of ḥadīth sciences affirmed by the scholars; neglecting the sayings of scholars regarding the commentary of the ḥadīth; not consulting the language lexicography; omitting the appropriate meaning of the ḥadīth context; and the lack of adherence to the scholars’ approach in understanding the ḥadīth through collecting and studying the narratives. Several conclusions were reached, including: the clear absence of the scientific methodology in the practice of the accusers; and the boldness of the accusers in dealing with the sunnah while they are unequipped with the necessary scientific tools. Moreover, most of the contemporary accusers, if not all of them, are not specialised in ḥadīth science, and therefore, they separate completely between the ḥadīth text and the accurate readings in order to properly understand and interpret the narratives within the Islamic heritage. However, the worst feature within their approach is that they favour the authority of reason over the divine text, especially in dealing with the ḥadīth of the unseen.